A rare case of heterotopic quintuplets pregnancy - Dennis Wu; Ling-Yien Hii; S.W. Steven Shaw (Elsevier, 2019)
Objective: We report a rare case of heterotopic pregnancy and high-order pregnancy occurring simultaneously following the use of the assisted reproductive technique (ART). Case report: A 29-year-old woman, Gravida 2 Para 1, became pregnant after receiving intrauterine insemination (IUI). She came to our emergency room due to diffuse low abdominal pain at seven weeks of gestational age. Transabdominal sonography (TAS) revealed a quadruplet intrauterine pregnancy with an enlarged left adnexa and intrapelvic fluid accumulation. Simultaneous occurrence of high-order pregnancy and left tubal pregnancy with internal hemorrhage was suspected. The patient received an emergent laparoscopic resection of the affected Fallopian tube and recovered well for the remaining hospitalization course. Afterwards, she received fetal reduction procedure and eventually gave birth to twin babies. Conclusion: Gynecologist should increase the awareness of heterotopic pregnancy in patients receiving ART. On the other hand, reproductive endocrinologist should reduce the risk of high-order pregnancy without compromising pregnancy rate. Keywords: Assisted reproductive technology, Heterotopic pregnancy, High-order multiple gestation, Intrauterine insemination, Ovulation induction